1986
DOI: 10.1111/j.2042-3306.1986.tb03695.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of arterial blood pressure in newborn foals using an electronic sphygmomanometer

Abstract: Summary An electronic sphygmomanometer which functions on oscillometric principles, was used to measure arterial blood pressure in foals. Its accuracy was assessed by comparison with results obtained by direct measurement in anaesthetised pony foals, aged 34 to 64 days. Correlations between data obtained by the two methods were highly significant but the sphygmomanometric readings were consistently lower than those obtained by direct measurement. An equation was derived from the pooled values for mean, systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 8 publications
2
17
1
Order By: Relevance
“…The NIBP technique at the MC and RU consistently underestimated IBP. This is consistent with assessment of NIBP in foals in which measurements over the median artery were consistently lower than with the invasive MAP [23]. The inaccurate results of NIBP at the MC agree with a study assessing NIBP measurements at the metacarpus in camelids, which found marked differences between invasive and noninvasive measurements [24].…”
Section: Discussionsupporting
confidence: 86%
“…The NIBP technique at the MC and RU consistently underestimated IBP. This is consistent with assessment of NIBP in foals in which measurements over the median artery were consistently lower than with the invasive MAP [23]. The inaccurate results of NIBP at the MC agree with a study assessing NIBP measurements at the metacarpus in camelids, which found marked differences between invasive and noninvasive measurements [24].…”
Section: Discussionsupporting
confidence: 86%
“…For instance, non-invasive systemic arterial pressure measurements are known to generate lower values than invasive measurements in animals (Franco et al, 1986). The site of the pressure measurements is also a factor which should be considered, because pressure values at any point above or under the heart level are influenced by a hydrostatic effect (Detweiler, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…If indirect techniques such as ultrasonic Doppler recording or electronic sphygmomanometry are used, calculated MAP may be as low as 50 mmHg in normal one-day-old foals, rising to 60 to 70 mmHg at age 2-3 weeks (Lombard et al 1984). Regardless of the technique used, pony foals (Lombard et al 1984) have a slightly lower arterial blood pressure than Thoroughbred foals (Franco et al 1986). Direct measurement of MAP via an arterial catheter reveals consistently higher values (Franco et al 1986), but a steady increase in blood pressure with age is still apparent.…”
Section: Mean Arterial Blood Pressure (Map) Values Dependmentioning
confidence: 99%